How do you prove $\dfrac{1+\cos x}{\sin x}+\dfrac{\sin x}{1+\cos x}=\csc x$ ?
Answer
Verified
454.8k+ views
Hint: We begin from left hand side of the given statement by adding the two fractional trigonometric expressions by the working rule to add fractions$\dfrac{a}{b}+\dfrac{c}{d}=\dfrac{ad+bc}{bd}$ and then use Pythagorean trigonometric identity ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1$ to simplify. We finally use the reciprocal relation between sine and cosine $\csc \theta =\dfrac{1}{\sin \theta }$ to arrive at the right hand side.
Complete step-by-step solution:
We are given the following statement to prove.
\[\dfrac{1+\cos x}{\sin x}+\dfrac{\sin x}{1+\cos x}=\csc x\]
We begin from left hand side using the working rule for adding fraction $\dfrac{a}{b}+\dfrac{c}{d}=\dfrac{ad+bc}{bd}$ for $a=1+\cos x=d,b=\sin x=c$ have;
\[\begin{align}
& \dfrac{1+\cos x}{\sin x}+\dfrac{\sin x}{1+\cos x} \\
& \Rightarrow \dfrac{\left( 1+\cos x \right)\left( 1+\cos x \right)+\sin x\cdot \sin x}{\sin x\left( 1+\cos x \right)} \\
& \Rightarrow \dfrac{{{\left( 1+\cos x \right)}^{2}}+\sin x\cdot \sin x}{\sin x\left( 1+\cos x \right)} \\
\end{align}\]
We use the algebraic identity ${{\left( a+b \right)}^{2}}={{a}^{2}}+{{b}^{2}}+2ab$ in the numerator of the above step for $a=1,b=\cos x$to have;
\[\begin{align}
& \Rightarrow \dfrac{1+{{\cos }^{2}}x+2\cdot 1\cdot \cos x+{{\sin }^{2}}x}{\sin x\left( 1+\cos x \right)} \\
& \Rightarrow \dfrac{1+{{\sin }^{2}}x+{{\cos }^{2}}x+2\cos x}{\sin x\left( 1+\cos x \right)} \\
\end{align}\]
We know from Pythagorean trigonometric identity that ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1$ for all values of $\theta $. We use this identity in numerator the above step for $\theta =x$to have
\[\begin{align}
& \Rightarrow \dfrac{1+1+2\cos x}{\sin x\left( 1+\cos x \right)} \\
& \Rightarrow \dfrac{2+2\cos x}{\sin x\left( 1+\cos x \right)} \\
& \Rightarrow \dfrac{2\left( 1+\cos x \right)}{\sin x\left( 1+\cos x \right)} \\
\end{align}\]
We cancel out the term $1+\cos x$ in the numerator and denominator of the above step to have;
\[\Rightarrow \dfrac{2}{\sin x}\]
We use the reciprocal relation of sine and cosecant $\csc \theta =\dfrac{1}{\sin \theta }$ for $\theta =x$ in the above step to have
\[\Rightarrow \dfrac{2}{\sin x}=2\csc x\]
The above expression is on the right hand side of the statement of proof. Hence the given statement is proved.
Alternative Method: We shall alternatively solve using cosine and sine double angle formulas. We know that the double angle formula of cosine $1+\cos \theta =2{{\cos }^{2}}\left( \dfrac{\theta }{2} \right)$. We know from the sine double angle formula that $\sin 2\theta =2\sin \theta \cos \theta $. We use this formula in the left hand side of the given expression and then proceed to have;
\[\begin{align}
& \dfrac{2{{\cos }^{2}}\left( \dfrac{x}{2} \right)}{2\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)}+\dfrac{2\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)}{2{{\cos }^{2}}\left( \dfrac{x}{2} \right)} \\
& \Rightarrow \dfrac{\cos \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)}{\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)}+\dfrac{\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)}{\cos \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)} \\
\end{align}\]
We cancel out the term $\cos \left( \dfrac{x}{2} \right)$ in the above step to have;
\[\begin{align}
& \Rightarrow \dfrac{\cos \left( \dfrac{x}{2} \right)}{\sin \left( \dfrac{x}{2} \right)}+\dfrac{\sin \left( \dfrac{x}{2} \right)}{\cos \left( \dfrac{x}{2} \right)} \\
& \Rightarrow \dfrac{{{\cos }^{2}}\left( \dfrac{x}{2} \right)+{{\sin }^{2}}\left( \dfrac{x}{2} \right)}{\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)} \\
\end{align}\]
We use the Pythagorean trigonometric identity that ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1$ for $\theta =\dfrac{x}{2}$ in the above step to have;
\[\begin{align}
& \Rightarrow \dfrac{1}{\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)} \\
& \Rightarrow \dfrac{2}{2\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)} \\
\end{align}\]
We use the sine double angle formula $\sin 2\theta =2\sin \theta \cos \theta $ for $\theta =\dfrac{x}{2}$ in the denominator of above step to have;
\[\begin{align}
& \Rightarrow \dfrac{2}{\sin \left( 2\times \dfrac{x}{2} \right)} \\
& \Rightarrow \dfrac{2}{\sin x} \\
& \Rightarrow 2\times \dfrac{1}{\sin x} \\
\end{align}\]
We use the reciprocal relation of sine and cosecant $\csc \theta =\dfrac{1}{\sin \theta }$ for $\theta =x$ in the above step to have
\[\Rightarrow 2\times \csc x=2\csc x\]
The above expression is on the right hand side of the statement of proof. Hence the given statement is proved.
Note: We note that an equation is called identity when the expression is true for all values of parameters $x$. We see that in the given expression assumes conditions $\sin x\ne 0\Rightarrow x=n\pi $ and $1+\cos x\ne 0\Rightarrow c\ne \left( 2n+1 \right)\pi $ where $n$ is any integer. So the given equation is not an identity. We need to be clear of the confusion between formulas $1+\cos \theta ={{\cos }^{2}}\left( \dfrac{\theta }{2} \right)$ and $1-\cos \theta ={{\sin }^{2}}\left( \dfrac{\theta }{2} \right)$ by remembering that in most formulas negative sign is associated with sine and positive sign associated with cosine.
Complete step-by-step solution:
We are given the following statement to prove.
\[\dfrac{1+\cos x}{\sin x}+\dfrac{\sin x}{1+\cos x}=\csc x\]
We begin from left hand side using the working rule for adding fraction $\dfrac{a}{b}+\dfrac{c}{d}=\dfrac{ad+bc}{bd}$ for $a=1+\cos x=d,b=\sin x=c$ have;
\[\begin{align}
& \dfrac{1+\cos x}{\sin x}+\dfrac{\sin x}{1+\cos x} \\
& \Rightarrow \dfrac{\left( 1+\cos x \right)\left( 1+\cos x \right)+\sin x\cdot \sin x}{\sin x\left( 1+\cos x \right)} \\
& \Rightarrow \dfrac{{{\left( 1+\cos x \right)}^{2}}+\sin x\cdot \sin x}{\sin x\left( 1+\cos x \right)} \\
\end{align}\]
We use the algebraic identity ${{\left( a+b \right)}^{2}}={{a}^{2}}+{{b}^{2}}+2ab$ in the numerator of the above step for $a=1,b=\cos x$to have;
\[\begin{align}
& \Rightarrow \dfrac{1+{{\cos }^{2}}x+2\cdot 1\cdot \cos x+{{\sin }^{2}}x}{\sin x\left( 1+\cos x \right)} \\
& \Rightarrow \dfrac{1+{{\sin }^{2}}x+{{\cos }^{2}}x+2\cos x}{\sin x\left( 1+\cos x \right)} \\
\end{align}\]
We know from Pythagorean trigonometric identity that ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1$ for all values of $\theta $. We use this identity in numerator the above step for $\theta =x$to have
\[\begin{align}
& \Rightarrow \dfrac{1+1+2\cos x}{\sin x\left( 1+\cos x \right)} \\
& \Rightarrow \dfrac{2+2\cos x}{\sin x\left( 1+\cos x \right)} \\
& \Rightarrow \dfrac{2\left( 1+\cos x \right)}{\sin x\left( 1+\cos x \right)} \\
\end{align}\]
We cancel out the term $1+\cos x$ in the numerator and denominator of the above step to have;
\[\Rightarrow \dfrac{2}{\sin x}\]
We use the reciprocal relation of sine and cosecant $\csc \theta =\dfrac{1}{\sin \theta }$ for $\theta =x$ in the above step to have
\[\Rightarrow \dfrac{2}{\sin x}=2\csc x\]
The above expression is on the right hand side of the statement of proof. Hence the given statement is proved.
Alternative Method: We shall alternatively solve using cosine and sine double angle formulas. We know that the double angle formula of cosine $1+\cos \theta =2{{\cos }^{2}}\left( \dfrac{\theta }{2} \right)$. We know from the sine double angle formula that $\sin 2\theta =2\sin \theta \cos \theta $. We use this formula in the left hand side of the given expression and then proceed to have;
\[\begin{align}
& \dfrac{2{{\cos }^{2}}\left( \dfrac{x}{2} \right)}{2\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)}+\dfrac{2\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)}{2{{\cos }^{2}}\left( \dfrac{x}{2} \right)} \\
& \Rightarrow \dfrac{\cos \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)}{\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)}+\dfrac{\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)}{\cos \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)} \\
\end{align}\]
We cancel out the term $\cos \left( \dfrac{x}{2} \right)$ in the above step to have;
\[\begin{align}
& \Rightarrow \dfrac{\cos \left( \dfrac{x}{2} \right)}{\sin \left( \dfrac{x}{2} \right)}+\dfrac{\sin \left( \dfrac{x}{2} \right)}{\cos \left( \dfrac{x}{2} \right)} \\
& \Rightarrow \dfrac{{{\cos }^{2}}\left( \dfrac{x}{2} \right)+{{\sin }^{2}}\left( \dfrac{x}{2} \right)}{\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)} \\
\end{align}\]
We use the Pythagorean trigonometric identity that ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1$ for $\theta =\dfrac{x}{2}$ in the above step to have;
\[\begin{align}
& \Rightarrow \dfrac{1}{\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)} \\
& \Rightarrow \dfrac{2}{2\sin \left( \dfrac{x}{2} \right)\cos \left( \dfrac{x}{2} \right)} \\
\end{align}\]
We use the sine double angle formula $\sin 2\theta =2\sin \theta \cos \theta $ for $\theta =\dfrac{x}{2}$ in the denominator of above step to have;
\[\begin{align}
& \Rightarrow \dfrac{2}{\sin \left( 2\times \dfrac{x}{2} \right)} \\
& \Rightarrow \dfrac{2}{\sin x} \\
& \Rightarrow 2\times \dfrac{1}{\sin x} \\
\end{align}\]
We use the reciprocal relation of sine and cosecant $\csc \theta =\dfrac{1}{\sin \theta }$ for $\theta =x$ in the above step to have
\[\Rightarrow 2\times \csc x=2\csc x\]
The above expression is on the right hand side of the statement of proof. Hence the given statement is proved.
Note: We note that an equation is called identity when the expression is true for all values of parameters $x$. We see that in the given expression assumes conditions $\sin x\ne 0\Rightarrow x=n\pi $ and $1+\cos x\ne 0\Rightarrow c\ne \left( 2n+1 \right)\pi $ where $n$ is any integer. So the given equation is not an identity. We need to be clear of the confusion between formulas $1+\cos \theta ={{\cos }^{2}}\left( \dfrac{\theta }{2} \right)$ and $1-\cos \theta ={{\sin }^{2}}\left( \dfrac{\theta }{2} \right)$ by remembering that in most formulas negative sign is associated with sine and positive sign associated with cosine.
Recently Updated Pages
Can anyone list 10 advantages and disadvantages of friction
What are the Components of Financial System?
How do you arrange NH4 + BF3 H2O C2H2 in increasing class 11 chemistry CBSE
Is H mCT and q mCT the same thing If so which is more class 11 chemistry CBSE
What are the possible quantum number for the last outermost class 11 chemistry CBSE
Is C2 paramagnetic or diamagnetic class 11 chemistry CBSE
Trending doubts
The correct order of melting point of 14th group elements class 11 chemistry CBSE
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
What is the specific heat capacity of ice water and class 11 physics CBSE
State the laws of reflection of light
The dimensional formula of dielectric strength A M1L1T2Q class 11 physics CBSE
The members of the Municipal Corporation are elected class 11 social science CBSE